Вы находитесь на странице: 1из 3

.

I.
Th


f (x) g(x) :
1. f g (a; b), a b ;
2. lim f (x) = lim g(x) = 0
xa+

xa+

3. g 0 (x) 6= 0 (a; b)
f 0 (x)
0
xa+ g (x)

4. lim

f (x)
xa+ g(x)

lim
I

=AR
f 0 (x)
.
0
xa+ g (x)

= A = lim

a , .. , .
, ,
, (
) .
, f (a) = g(a) = 0 ( ,
?! , ,
,

).
x (a; b). x a f g ( , ).
:
f (x) 0
f (x) f (a)
f 0 ()
f (x)
=
=
= 0 ,
(1)
g(x)
g(x) 0
g(x) g(a)
g ()
(a; x). x (a; b)
, x, x
.
, :
0

f (x)

0+

> 0 : () > 0 : x U 0
A <
(2)
g (x)
x U0+ x (a; x), , ..
x U0+ , U0+ . , x :
f (x)
f 0 ()
= 0
g(x)
g ()

(3)

, .. U0+ ,
0



f ()

f (x)


<
< ,

A
g 0 ()

g(x)


.

(4)

.
1. .
t = x1 0


f 1t
= f 0 1t t12 .
, ,
(, , , ). ,
, ,
, ,
R1 1.

2. , , , ,

( , - , ,
).

II.


:
f (x)
=
g(x)

1
g(x)
1
f (x)

0
0

(5)


-
( , ).
, :
Th
f (x) g(x) :
1. f g (a; b), a b ;
2. lim f (x) = lim g(x) =
xa+

xa+

3. g 0 (x) 6= 0 (a; b)
f 0 (x)
0
xa+ g (x)

4. lim

f (x)
xa+ g(x)

lim
I

=AR
f 0 (x)
.
0
xa+ g (x)

= A = lim

, A 6 0 (
).
(0; 41 ). 0 (x)
x (a; b) : x (a; x ) fg0 (x)
U (A) (,
. x = a + , ,
).

(a; x ) x. :
f (x) f (x )
f 0 ()
= 0 , a < x < < x < b
g(x) g(x )
g ()

(6)

:
f (x )
g(x )
f (x) 1 f (x)
f 0 ()
f (x)
f 0 () 1 g(x)
= 0

= 0

g(x) 1 g(x )
g ()
g(x)
g () 1 f (x )
g(x)
f (x)

(7)

: x a ( x a a (6)). ,
)
. , lim ff(x
= 0, .. f (x ) = const.
(x)
xa+





() > 0 : x
f (x )
g(x )
(a; a + ), + a < b f (x) < , g(x) < .
:


)
1 g(x
1 1+
g(x)
;
;
(8)

)
1+ 1
1 ff(x
(x)
, ,
0 (x)
2
1+
= 1 + 1
< 1 + 83 . fg0 (x)
U (A), :
1 2 1

1
1+

2
= 1 1+
>




g(x )
f (x)
f 0 () 1 g(x)
8
= 0

(A ) (1 2); (A + ) 1 +
=
g(x)
g () 1 f (x )
3
f (x)


8
8 2
2
= A ( + 2A 2 ); A + ( + A + )
3
3

8
8
f (x)
U (A), = max{ + 2A 22 ; + A + 2 } (9)
g(x)
3
3

, lim = 0 ( 0

), .. ,
( , ),
.

, A.
.
. , a .
, -
, , ,
. .
!

Оценить